Evaluation of moderately grafted primary, diamine, and triamine sorbents for CO2 adsorption from ambient air: balancing kinetics and capacity under humid conditions - Wadi, Basil; Golmakani, Ayub; Manovic, Vasilije; Nabavi, Seyed Ali (American Chemical Society, 2021)
Successful deployment of direct air capture (DAC) to mitigate the consequences of climate change depends on many factors, one of which is the development of kinetically efficient CO2 sorbents with a high sorption capacity, at ultralow CO2 concentrations. This work evaluated CO2 adsorption performance of primary-, diamine-, and triamine-grafted SBA-15 at pressures below 5 kPa for DAC applications, measured through volumetric sorption, followed by humid air (23% RH) adsorption by gravimetric analysis. Under humid air flow, triamines at an amine loading of 4.6 mmol/g showed the highest enhancement in adsorption, with an uptake of 26 mg/g, but the slowest average adsorption rate of 216 μg/g/min. Diamine at an amine loading of 2.78 mmol/g had an adsorption rate of 295 μg/g/min but demonstrated the lowest uptake of 13 mg/g. In comparison, primary amines at a loading of 2.6 mmol/g reached an equilibrium uptake of 22 mg/g, with a higher adsorption rate of 354 μg/g/min. Triamine grafted at 3.5 mmol/g had the fastest kinetics of all samples, reaching 525 μg/g/min. Results indicated that primary amines and moderate-to-high density triamine reagents incorporated into mesoporous media can offer a superior adsorption rate that can make up for lower adsorption capacities, by optimizing cyclic performance, and should be considered when designing for continuous DAC processes.
Keywords: Atmospheric chemistry; Amines; Adsorption; Silica; Materials